THE SOCIO-CULTURAL DETERMINANTS OF THE SHADOW ECONOMY IN MODERN RUSSIAN SOCIETY - Lizina, Olga; Bistyaykina, Dinara; Ermakova, Eka; Badokina, Tatiana; Solovyeva, Tatyana (Revista Inclusiones, 2020)
Studies of the shadow economy are not only of scientific but also practical significance. The level of development of the shadow economy is important from the perspective of the development of any state; it determines the goals and priorities of state development. Shadow economy is one of the leading problems in Russia, which undermines the political system and poses a serious threat to the social security of the country. The aim of this work is to analyze the main social factors in the spread of the shadow economy throughout the Russian Federation. The article suggests and analyzes an original approach to measuring the shadow economy in the socio-cultural space. The research is based on factor analysis of official statistics showing over 300 indicators that characterize different spheres of state functioning collected in Russia from 1992 to 2019. The factors influenced by the shadow economy are identified.